Comparison Among Alpha-tricalcium Phosphate Synthesized by Solid State Reaction and Wet Chemical Reaction for Calcium Phosphate Cements - Paritat Thaitalay (Science Faculty of Chiang Mai University, 2019)
Recently, calcium phosphate cement has been used in bone tissue engineering and regenerative medicine due to its bioactivity and biocompatibility. Alpha-tricalcium phosphate has been known previously to be an essential raw material of self-setting calcium phosphate cement. The most established method for alpha-tricalcium phosphate synthesis is the solid state reaction of Dicalcium phosphate anhydrous (DCPA) and Calcium carbonate (CaCO3) at high temperatures, follow by quenching immediately to room temperature. It has been reported that alpha-tricalcium phosphate synthesized by wet chemical reaction from calcium nitrate (Ca(NO3)2×4H2O) and phosphoric acid (H3PO4) at high temperature, being unnecessary quenching for obtaining high purity alpha-tricalcium phosphate. The aim of the present work was to study the effect of comparative alpha-tricalcium phosphate powder obtained by solid state reaction and wet chemical reaction on the properties of calcium phosphate cements. The obtained powder was characterized by particle size analysis and X-ray diffraction. Cement powders consisting of the different synthesis of alpha-tricalcium phosphate powders were mixed with the liquid solution to obtain cement paste. After setting cement samples were determined by setting time, compressive strength, phase analysis in vitro test (simulated body fluid). Although the calcium phosphate cement was prepared using alpha-tricalcium phosphate by solid state reaction showed a slightly better performance, it was likely that the resulting cement from both syntheses was not significantly different.